Meso-fracture mechanism of Longmaxi shale with different crack-depth ratios: Experimental and numerical investigations. (November 2021) - Lei, Bo; Li, Hongtao; Zuo, Jianping; Liu, Haiyan; Yu, Meilu; Wu, Genshui
Highlights: Based on the in-situ SEM experiment, the full fracture process and mesoscale crack propagation mode of shale were discussed in detail. Based on double-K fracture criterion, the subcritical crack length, initial and unstable fracture toughness were calculated theoretically. The fracture morphology characteristics of Longmaxi shale were deeply investigated. The effect of the sedimentary particle and bedding plane on crack propagation has been simulated based on particle flow code. Abstract: The mechanical properties and fracture mechanism of shale are vital to the design of hydraulic fracturing schemes. To better understand the formation and evolution of hierarchical crack networks in shales, a scanning electron microscope (SEM) with a loading device was applied to carry out three-point bending experiment on Longmaxi shale with different crack-depth ratios (CDR). The micro-damage and fracture processes of shale were observed in situ. Based on the double-K fracture criterion, the subcritical crack length, and the initial and unstable fracture toughness were calculated theoretically. The results demonstrated that the crack initial load, peak load, and subcritical crack length decreased significantly with the increase of the CDR. Both the initial and unstable fracture toughness were relatively stable when the CDR was between 0.3 and 0.5, and they can be regarded as constants. The meso -failure mechanism of shale was tensile and shear failure, and fracture patterns were inter-granular, trans -granular and coupled fracture. Generally, tensile failure typically results in irregular rough sections, whereas shear failure results in smooth sections with parallel slip lines. The micropores inside and between the crystals can induce the connection and penetration of cracks. The initiation of microcracks is the result of the continuous accumulation and nucleation of multiple micro/ nanoscale damage, and the tortuous crack path is caused by the variation in the local stress field at the crack tip. In addition, clump and smooth joint model (SJM) were introduced to simulate the effect of the sedimentary particle and bedding plane on crack propagation based on particle flow code in two dimensions (PFC2D). The simulation results were in good agreement with the experimental observations.